Given the equation:
![T\mleft(h\mright)=48.5-2.5h](https://img.qammunity.org/2023/formulas/mathematics/college/3ej6k568texhjqtmg42hfacbb6ma290r3p.png)
where: (h) is the height above the planet's surface in kilometers.
T(h) is the temperature in Celsius.
If we have calculated the function:
![h=T^(-1)(x)](https://img.qammunity.org/2023/formulas/mathematics/college/miyfsuthran39yewsfiujern86udn59mnr.png)
(a)
so, the output is the last function will be the height above the planet's surface.
So, the statements that best describe the last function is:
(b) the expression for the last function will be as follows:
![\begin{gathered} x=48.5-2.5h \\ 2.5h=48.5-x \\ h=(1)/(2.5)(48.5-x) \\ \\ h=19.4-0.4x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/41dsy2p34vq2hwgla93a0xcr2cijahyn5a.png)
so, the answer for part (b) is:
![T^(-1)(x)=19.4-0.4x](https://img.qammunity.org/2023/formulas/mathematics/college/1tq7zt6h0nshym46k3fulqwgyr83l64odq.png)
Part (c): we need to find:
![T^(-1)(33)=\text{?}](https://img.qammunity.org/2023/formulas/mathematics/college/dxx8lroyo9w0cb2ql3nb0p3z0e8d8pd0v5.png)
So, By substitution with x = 33 into the equation of part (a) as follows:
![\begin{gathered} T^(-1)(33)=19.4-0.4\cdot33 \\ \\ T^(-1)(33)=6.2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2nr9qms6ikdiw7v2bjgksrwv3okyd3ye29.png)
so, the answer of part (c) = 6.2